Questionable peer review practices - Sasaki, Kyoshiro (2024)
Background. Peer review is a crucial system in academic publishing. However, this system is often undermined by certain malpractices. Objective. This paper discusses questionable peer review practices (QPRPs) that undermine the efficacy of peer review systems in academic publishing. Methods. We highlight several cases of QPRPs and their impact on the integrity of the publication process and the quality of scientific discourse. Results. Considering QPRPs and their impact, we propose solutions, including implementing open peer review, enhancing the role of editors, adopting crowd peer review, and promoting the Registered Reports system. Additionally, we advocate for comprehensive peer review training and emphasize the importance of understanding, rather than penalizing, unintentional QPRPs. Contribution. Our discussion aims to contribute to ongoing discussions on improving the peer review process and ensuring the reliability of published research.